Transformational Leadership and Educational Quality: Strengthening Teacher Motivation and Commitment in Islamic Education - Shera Nabila Luvianingtias; Rahayu Lestari; Nur Fahmuddin Hanif; Nirva Diana; Eti Hadiati; Muhammad Safdar Bhatti; Ifedayo Emmanuel Adu (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
This study examines the role of transformational leadership in improving educational quality, with particular emphasis on teacher motivation and commitment in Islamic educational institutions. The research employs a Systematic Literature Review (SLR) following PRISMA guidelines to analyze 28 peer-reviewed journal articles published within the last ten years. The selection process was based on relevance to transformational leadership, educational quality, and Islamic educational contexts. The analysis focuses on four core dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The findings reveal that these dimensions consistently contribute to increased teacher engagement, stronger organizational commitment, improved professional development, and a more positive school climate, all of which are critical indicators of educational quality. The study also highlights that integrating transformational leadership practices with Islamic educational values strengthens institutional identity while responding to contemporary educational challenges. This research contributes by synthesizing recent scholarship into a structured conceptual understanding of how transformational leadership supports educational reform in Islamic institutions. It further recommends the development of targeted leadership training programs to enhance strategic leadership capacity and sustain long-term educational improvement.